2000
DOI: 10.1093/ije/29.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Serological analysis of a cryptosporidiosis epidemic

Abstract: These elevated serological responses indicate that Cryptosporidium infections among Collingwood residents likely occurred more commonly than illness reports suggested, consistent with a community-wide cryptosporidiosis epidemic. Similar studies should be considered in future suspected cryptosporidiosis epidemic investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 8 publications
2
22
1
Order By: Relevance
“…Serum antibody responses to the gp15/15-17-kD antigen have been reported in children with cryptosporidiosis in developing countries 21 in children and adults after outbreaks of cryptosporidiosis [35][36][37] and in adults infected with human immunodeficiency virus in developed countries. 38 However, all of these studies used partially purified native C. parvum 17-kD antigen or C. parvum lysate as antigen in ELISA or immunoblots.…”
Section: Discussionmentioning
confidence: 99%
“…Serum antibody responses to the gp15/15-17-kD antigen have been reported in children with cryptosporidiosis in developing countries 21 in children and adults after outbreaks of cryptosporidiosis [35][36][37] and in adults infected with human immunodeficiency virus in developed countries. 38 However, all of these studies used partially purified native C. parvum 17-kD antigen or C. parvum lysate as antigen in ELISA or immunoblots.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, given the higher attack rate for diarrheal illness among adults in the greater Milwaukee area (28% for persons у20 years old), compared with that among children (19% for children !10 years old) [10], it seems likely that the antibody by guest on March 22, 2015 http://jid.oxfordjournals.org/ Downloaded from prevalence among adults would be comparable in magnitude to that among the children. In fact, Frost et al [16] recently demonstrated that, in the weeks after the 1996 outbreak of cryptosporidiosis in Collingwood, Ontario, Canada, 69% and 88% of the adult residents who were tested by Western blot assay were positive for antibodies to the 17-and 27-kDa C. parvum antigens, respectively [16]. Both the fraction of positive residents and the mean antibody responses to these 2 markers were higher in residents of Collingwood than in residents of Toronto, where no outbreak occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the unbalanced frequency of outbreaks between the European continent and the other countries cited above could be an immunological protection against Cryptosporidium in individuals on the European continent. Indeed, a recent study has shown a high prevalence of serological response to Cryptosporidium in Italian individuals, which could explain the infrequent occurrence of clinically detectable cryptosporidiosis in an Italian city (13).…”
Section: Discussionmentioning
confidence: 99%